What Is the Burden of Immunoglobulin Replacement Therapy in Adult Patients With Primary Immunodeficiencies? A Systematic Review - Jones, Georgina L.; Vogt, Katharina S.; Chambers, Duncan; Clowes, Mark; Shrimpton, Anna (Frontiers in Immunology, 2018)
Background: Primary immunodeficiency disorders (PIDs) are a group of heterogeneous rare disorders, whereby the immune system is missing or not functioning adequately. For patients requiring treatment, the most common option is Immunoglobulin replacement therapy (Ig). Treatment of PIDs is simultaneously associated with both, improvements in health-related quality of life as well as increased treatment burden. This review sought to review studies investigating the burden of Ig treatment, synthesise evidence in relation to administration routes (subcutaneous or intravenous) and instruments used; as well as make recommendations for clinical and research applications in this area for patients aged 16 years and older. Methods: We searched Medline, EMBASE and The Cochrane Library. Sifting of titles was performed by two reviewers, and the assessment of full-text articles by three. From a database which contained 3770 unique results, sixty-seven full texts were reviewed. Eventually, 17 studies were found to meet the inclusion criteria, and included in this review. Due to data heterogeneity, a narrative, descriptive synthesis of the evidence was undertaken. Results: Most studies were carried out in the USA/North America, used a prospective observational design and involved patients with Common Variable Immune Deficiency. Four studies measured the burden of receiving IVIg therapy and 13 measured SCIg therapy. A wide range of measures, primarily designed to measure aspects of treatment satisfaction (e.g. Life Quality Index or a slightly modified version) and health-related quality of life (e.g. The SF-36) had been used. Discussion: Lack of a parallel control group in most studies meant that changes in outcomes could be due to factors other than changes in the treatment regimen. However, overall, PID patients appeared to report little Ig treatment burden and were satisfied with either modality. However, patient preference appeared to be the delivery of the Ig treatment in the patient’s home and SCIg was preferred after switching from IVIg therapy. Individual differences appeared to affect treatment preference and therefore understanding the decision support needs of PID patients facing IG treatment choices would be valuable. Using a questionnaire specifically designed to measure the patient’s perspective of Ig treatment burden is recommended in future research.